2000
DOI: 10.1128/iai.68.10.5816-5823.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Lactoferrin and Peptides Derived from a Surface-Exposed Helical Region Reduce ExperimentalEscherichia coliUrinary Tract Infection in Mice

Abstract: Escherichia coli bacteria into the urinary bladder. The control groups received phosphate-buffered saline or water. C3H/Tif mice were treated with hLF or bLF, and C3H/HeN mice were treated with bLF only. The numbers of bacteria in the kidneys and bladder of C3H/Tif and C3H/HeN mice were significantly reduced 24 h later by the LF treatments compared to the findings for the control group. The hLF-treated group showed the strongest reduction compared with the vehicle-treated-group (P values were 0.009 and 0.0001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 37 publications
5
78
0
3
Order By: Relevance
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to play an important role in host defence because it exhibits a variety of biological activities, including antimicrobial activity and immunomodulatory effects, as shown by in-vitro studies [1,2]. It is increasingly appreciated that oral administration of LF or its fragment peptides improves the survival rate and enhances elimination of pathogens from the body of animals or human patients infected with bacteria, fungi, protozoa or viruses [3][4][5][6][7]. Recent studies showed that feeding bovine LF enhances the elimination of pathogens and the rate of symptomatic cure in guinea-pigs and man with dermatophytosis, a very common fungal infection on the skin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse experiments, oral administration of bovine LF reduced the number of bacterial infections in the gastrointestinal tract [23], while promoting the growth of bacteria with low iron requirements such as Lactobacillus and Bifidobacterium, which are generally believed to be beneficial to the host [24,25]. Oral LF was also found to be effective against experimentally induced Urinary tract infection (UTI) and endotoxin-induced septic shock [26,27]. LF also has immune-modulatory role, ascribed to its immunotropic and antiinflammatory effects [28,29].…”
Section: Function and Spectrummentioning
confidence: 92%
“…LF or LFcin act synergistically against E. coli bacteria which are isolated from patients of bovine mastitis and human urinary tract infection [30,31]. Oral LF or derived peptides are also effective against E. coli uro-sepsis [26]. There is a presumptive hypothesis for this mechanism of action that the LF remains intact in the gastrointestinal tract and is accumulated in the blood only when the mucosal damage of GI system is seen leading to its breach in its integrity.…”
Section: Neonatal Sepsis and Lfmentioning
confidence: 99%